IMPLEMENTASI WEWENANG INTELIJEN PADA PROSES PENYELIDIKAN DUGAAN TINDAK PIDANA KORUPSI DALAM RANGKA PENEGAKAN HUKUM OLEH KEJAKSAAN NEGERI BENGKALIS - Prasetyo, Aditya Try; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the efforts of law enforcement in a criminal corruption is to do with the process of investigation which is the stage of preparation or one of the earliest stages. For it to help the process of the investigation, then established the intelligence agency in every country in the world, including Indonesia. Intelligence in law enforcement in Indonesia is divided into 5, namely the State Intelligence Agency, the intelligence of the Indonesian National Army, the intelligence Police of the Republic of Indonesia, the intelligence Prosecutor's office of the Republic of Indonesia, and intelligence ministries/government agencies non ministry. In fact the various regulations governing the eradication of criminal acts of corruption that have been made as well as the establishment of institutions to eradicate criminal acts of corruption still have not been able to eradicate corruption thoroughly.This study uses a typology of legal research of the sociological or legal research non-doctrinal, which is specifically discuss about the effectiveness of the law. In this study the author uses the descriptive research, because the author describes how the Implementation of the Implementation of the Authority of the Intelligence Prosecutor's office On the Process of Investigation of Alleged Corruption In Order to Law Enforcement By the State Attorney Bengkalis.The results of the research the author is, the first implementation of the implementation of the authority of the intelligence in the investigation of suspected criminal acts of corruption. Intelligence's duties and authority in collecting data and evidence whether the case belongs to the criminal event or not. And hopefully with the efforts made in exposing the alleged corruption case then it was expected no more or no addition of the numbers from year to year. And the implementation of the authority of the intelligence Prosecutor's office on the investigation of alleged corruption in order to law enforcement by the State Attorney Bengkalis is to collect data with a variety of ways to can be used as evidence about whether or not has occurred a criminal offence of corruption where the next evidence was submitted to the leaders or interested parties to the decision-making.Keywords: Implementation - intelligence authority - alleged corruption